Increasing the economic development of the EU countries through the implementation of the “Smart City” concept - But, Tetiana; Mamotenko, Daria (Management and Entrepreneurship: Trends of Development, 2025)
The implementation of the Smart City concept in the European Union is the largest research program developed and supported by the European Commission. The aim of the article is to study the implementation of the “Smart City” concept as a direction for enhancing the economic development of the European Union countries. The methodological basis of the study is formed by general scientific and special methods of economic theory, in particular, statistical and information reports of EС, the United Nations and world indicators of Smart Cities. The following measures have been identified to support the development of the Smart CIty concept: involvement of citizen science and civilian advisory councils; data protection through various European and international cybersecurity support programs; constant updating and creation of legislation based on environmental protection, transparency, security and fairness of online interaction; application of a cross-sectoral approach and disaggregated data; updating strategies for talent development, education and openness in trade, investment and exchange of experience; support for environmental and digital policy in the development of citywide or national Smart City strategies. The study reveals the reasons that hinder the implementation of the Smart City development concept in Europe: citizens’ lack of confidence to use digital tools to participate online; the impact of climate change and excessive environmental pressure, based on increased electricity and water consumption; and the growth of mining. The study of the relationship between the concepts of Industry 4.0 and Smart City has shown positive results of implementing the best practices of the EU countries in the innovation structures of the EU countries. To enhance the economic development of the EU countries through the implementation of the Smart City concept, it is proposed to implement a set of measures aimed at stimulating innovation, supporting small and medium-sized businesses, developing a green economy and improving energy efficiency. The practical significance of the results lies in the use of the recommendations provided, which will contribute to the economic development of the EU countries through the implementation of the “Smart City” concept and will have a positive impact on the environment, increase energy efficiency, improve the quality of life of the population and ensure the sustainable development of urban infrastructure in the EU countries. JEL Classification: О1, О2, О3, І31